Non-Medicinal Uses of Selected Wild Plants By The People of Mustang District, Nepal - Bhattarai, Sandesh; Chaudhary, R. P.; Taylor, R SL (Journal of Natural History Museum, 2009)
The local people of Mustang district use several wild plant species to fulfill various daily needs. Local people were interviewed during 2005-2007 regarding their uses of plants. We recorded several uses of 51 plant species (29 herbs,12 shrubs and 10 trees), belonging to 19 families under 31 genera. Among 51 species recorded, 23 species were used as fodder; followed by decoration materials and organic manure (nine species each). Plants were also used to make household articles, construction materials, recreational drugs, dye, soap, to make a beverage that is consumed as a substitute for tea and others. It is hoped that sustainable harvesting of these local resources will play an important role in in-situ conservation and ultimately help to maintain a sustainable ecosystem. Key words: Fodder; Mustang; Sustainable; Valuable resources; Wild plants Journal of Natural History Museum Vol. 24, 2009 Page 47-57